The All-I'll-ever-want Christmas Doll - McKissack, Pat 1944-; Pinkney, Jerry (New York : Schwartz & Wade Books, 2007)
During the Depression, three young sisters get one baby doll for Christmas and must find a way to share.
Keywords: Sharing -- Fiction; Sisters -- Fiction; Dolls -- Fiction; Christmas -- Fiction; Great Depression, 1929-1939 -- Fiction; African Americans -- Fiction